Pengembangan Website Desa Wisata untuk Optimalisasi Promosi Pariwisata di Desa Singapadu Kaler - Dewi, Ida Ayu Putri Diah Tantri; Utami, Nengah Widya; Alam, Helmy Syakh (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
A travel website is a website dedicated to tourist travel. One of the tourist villages in Bali is Singapadu Kaler Village, which is rich in cultural heritage, stunning nature and a fascinating diversity of traditions. Even though it has great potential as a tourist destination, Singapadu Kaler Village still faces challenges in communicating the charm and uniqueness of its place to tourists. With the above phenomenon, the author provides a solution to develop a tourism website that can help access information about tourism in Singapadu Kaler Village, Gianyar using the WordPress platform. Evaluation is carried out in two ways, namely using the SUS (System Usability Scale) method for users and the Summative Test for the Pokdarwis Chair. The evaluation results using the SUS method for users got a score of 80 and the evaluation results using the Summative Test for the Pokdarwis Chair showed that the Pokdarwis Chair already understood how to manage content and how WordPress works.